THE EFFECT OF FINANCIAL LITERACY, FINANCIAL MANAGEMENT BEHAVIOR, USE OF E-COMMERCE, AND PRODUCT INNOVATION ON MICRO BUSINESS PERFORMANCE IN PURBALINGGA REGENCY - Purbajati, Arya Dwi; Pratiwi, Umi; Budiarti, Laeli; Rafinda, Ascaryan; Sunarmo, Agus (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
This research aims to analyze the influence of financial literacy, financial management behavior, use of e-commerce, product innovation on the performance of micro businesses in Purbalingga Regency. The research method used is a quantitative approach. The population in this study were all members of the Purbalingga Batik Craftsmen Forum Association, totaling 257 members. The sample in this research were members of the Purbalingga Batik Forum Association who are included in the micro scale category, have a business age of at least 3 years, and have social media to support their business. This research collects data by distributing questionnaires directly to respondents. The data analysis used in this research is multiple linear regression analysis. The conclusion of this research shows that financial literacy and financial management behavior have no effect on the performance of micro businesses in Purbalingga Regency. However, the use of e-commerce and product innovation has an influence on the performance of micro businesses in Purbalingga Regency. The implication of this research is that business performance can increase if business actors increase financial literacy, carry out good financial management behavior, maximize the use of e-commerce to expand markets, and carry out product innovation so that consumers have a variety of choices from the products offered.